Cooperation and community rural Thailand : - Shigetomi, Shin'ichi (Institute of development economic, 1998)
This book presents the result of a study is presented of the cooperation that takes place among Thai villagers by examining their cooperative activities (such as savings groups, rice banks, and village cooperative shops) and the bases for these activities. The study found that the existence of a 'village community' has been a key element in supporting this new form of villager organizing. Through an analysis of self-organizing activities in rural development, the study points out the principles of Thai villager cooperation and the structure of their village community. It is also meant to be a contribution to the theoretical study of villager organizing which is vital to participatory development strategy.